Assessment of HIV knowledge and awareness in adults of a slum area of Mumbai, India: a cross-sectional study - Mehta, Varshil; Mehta, Sonali (International Journal Of Community Medicine And Public Health, 2017)
Background: HIV/AIDS is not only a health problem but also one of the most important social, economic, political and cultural problem. Previous studies have demonstrated low HIV knowledge and awareness among adults living in slum areas of India. The aim and objective of this study was to assess the extent of knowledge, attitude and awareness about HIV/AIDS in adults of urban slum area of Mumbai, India. Methods:A cross-sectional, quantitative, observational questionnaire-based survey on HIV-KQ-18 was conducted at one of the most populated slum area of Mumbai, India between July-September, 2015. The questionnaire comprised of 18 questions. Correct answers equal to or less than 13 meant low level of knowledge. Results: The present study showed that in general 67.77% of the adults gave more than 13 correct answers. Mean correct answers from males was 13.69 while that from females was 13.06 out of 18. Overall, females had less knowledge as compared to that of males. Adults in age group from 31 to 45 years had the maximum knowledge regarding HIV/AIDS followed by age group 18 to 30 and 45 to 60 years. Conclusions:Overall, the knowledge of HIV/AIDS in adults of urban slum was good and slightly better than the lower knowledge margin. The awareness of HIV has improved substantially over the last decade but it is not yet enough to prevent the spread of HIV. Further qualitative studies should be performed and new initiatives should be started in order to curb the ever increasing incidence and prevalance of HIV/AIDS.